2005
DOI: 10.1111/j.1600-0668.2005.00303.x
|View full text |Cite
|
Sign up to set email alerts
|

Size relationship between airborne viable bacteria and particles in a controlled indoor environment study

Abstract: Due to their respiratory health effects, determining exposure to airborne viable bacteria and particles of different sizes requires the study of their behavior in relation to each other. This study attempts to characterize the relationships of bacteria and particles that are predominantly of human origin. Findings of this work will help researchers in understanding how bacteria levels co-exist with particles of corresponding aerodynamic size across different size ranges between 20 degrees and 26 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(54 citation statements)
references
References 36 publications
5
49
0
Order By: Relevance
“…The results indicate that there were significant weak to strong positive correlations of bacterial concentrations to size-segregated NC at particle sizes of 1.6-17.5 µm and 25-32 µm (R = 0.233-0.625, p = 0.000-0.049), indicating that bacteria are widespread on fine and coarse particles. Our study produced similar results as other related studies (Oxborrow et al, 1975;Parat et al, 1999;Batterman, 2001;Tham and Zuraimi, 2005).…”
Section: Correlation Between Bacterial Bioaerosols and Ncsupporting
confidence: 82%
See 2 more Smart Citations
“…The results indicate that there were significant weak to strong positive correlations of bacterial concentrations to size-segregated NC at particle sizes of 1.6-17.5 µm and 25-32 µm (R = 0.233-0.625, p = 0.000-0.049), indicating that bacteria are widespread on fine and coarse particles. Our study produced similar results as other related studies (Oxborrow et al, 1975;Parat et al, 1999;Batterman, 2001;Tham and Zuraimi, 2005).…”
Section: Correlation Between Bacterial Bioaerosols and Ncsupporting
confidence: 82%
“…Bhangar et al (2016) indicated that each person generates 0.9-0.3 million coarse particle bioaerosols (2.5-10 µm) per hour, of which walking, sitting, physical activities of upper limbs, clothing, or the contact between clothing and skin are main sources. Tham and Zuraimi (2005) indicated that indoor viable bacteria with particle sizes of 1-2 µm exist alone, viable bacteria with particle sizes of 3-7.5 µm exist as aggregates, and viable bacteria with particle sizes > 7.5 µm originate from the shedding of human skin. Taking the results from other literature and our study together, there were significant weak to strong positive correlations of indoor airborne bacterial concentrations to size-segregated NC at particle sizes of 1.6-17.5 µm and 25-32 µm, respectively.…”
Section: Correlation Between Bacterial Bioaerosols and Ncmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial spores and cells are usually smaller, ranging from 1-5 µm. However, both fungi and bacteria can form spore chains or cell clusters or they can become attached to larger particles, such as clay or other soil particles, plant fragments or skin scales shed from human and animals (Tham and Zuraimi, 2005). All of the measured microbial groups were sporadically detected in the smallest size fraction (PM 0.2 ), which indicates that microbial fragments smaller than intact cells or spores are continually present in the indoor and outdoor air.…”
Section: Microbial Concentrationsmentioning
confidence: 99%
“…They observed that it was not possible to produce monodispersed single 28 nm aerosol particles, and that due to hydrophobic interactions between neighbouring protein capsids, viral particles tended to form large agglomerated structures during aerosolisation. Tham and Zuraimi [8] studied the indoor airborne viable bacteria of human origin. They found that at particle sizes between 3 and 7.5 lm, the bacteria exist as clumps.…”
Section: Introductionmentioning
confidence: 99%